(untitled) (El-Wahat Journal for Research and Studies, 2025)
Linguistic studies witnessed an important development, especially with what was stated by "Ferdinand Dussaucer", so pragmatics emphasizes the need to look at the use of language; therefore, this study seeks to focus on two procedures of pragmatics; verbs of speech and the implications of saying due to their influential function in the communicative process; through An applied study in Surat "Noah" Keywords: deliberative , verbs of speech , implications of saying Surah "Noah"